(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
System controls and monitoring has become a need in our households due to increase in use of modern applications and devices such as smart home security systems like CCTVs, E-lock systems, also other various appliances like smart lights, fans, air conditioners etc. The current solution for this is the smart wireless sensor network. This network use various monitoring setups like night visions, cameras, and infrared lasers. Also some are even designed to study the behavior pattern of the user and function accordingly. Electricity control of a building can be handled effectively with the help of sensor network. Such networks can be integrated in buildings, offices, homes for energy harvesting also its storage which can be used for the electronic components and circuit. The network can also be beneficial for the betterment of the living conditions of the home inhabitants by having a constant survelance for elderly and young children. As the system of networks is completely automated it reduces the human error and reduces energy consumption by optimizing it perfectly. Newer self-maintaining sensor networks can even enhance the security infrastructure of a home, office or an institute. This study further elobrate the functioning and uses of wireless sensor networks.